Real Neurolaw in the Netherlands: The Role of the Developing Brain in the New Adolescent Criminal Law - Schleim, Stephan (Frontiers in Psychology, 2020)
Previous publications discussed the conditions under which courts admitted or could admit neurotechnological evidence like brain scans. There were also first attempts to investigate legal decisions neuroscientifically. The present paper analyzes a different way in which neuroscience already influenced the law: The legal justification of the new Dutch adolescent criminal law explicitly mentions findings on brain development to justify a higher maximum age for the application of juvenile criminal law than before. The lawmaker’s reasoning is compared to the neuroscientific studies on which it is based. In particular, three neurodevelopmental publications quoted by the Dutch Council for the Administration of Criminal Justice and Protection of Juveniles to justify that adolescents can be less legally responsible are analyzed in detail. The paper also addresses possibilities under which brain research could improve legal decision-making in the future. One important aspect turns out to be that neuroscience should not only matter on the level of justification, but also provide better instruments on the individual level of application.